Impermanence and failure: the legacy of conservation-based payments in Sumatra, Indonesia - James T Erbaugh (Environmental Research Letters, 2022)
Projects that pay communities or individuals to conserve natural areas rarely continue indefinitely. When payments cease, the behaviors they motivate can change. Previous research on conservation-based payments recognizes the impermanence of conservation success, but it does not consider the legacy of payments that failed to effect change. This research assesses impermanence and failure by investigating the legacy of village-level conservation payments made through one of the largest Integrated Conservation and Development Projects in Indonesia. The Kerinci-Seblat Integrated Conservation and Development Project aimed to conserve forest area and promote local development through voluntary conservation agreements (VCAs) that provided payments for pro-conservation pledges and activities from 2000 through 2003. Project documentation and previous research find that payments failed to incentivize additional forest conservation, producing nonsignificant differences in forest-cover change during the project period. To examine the legacy of these payments in the post-project period, this research uses matched difference-in-differences and triple differences models to analyze forest cover change in villages ( n = 263) from 2000 through 2016 as well as matched binary logistic regression models to assess enduring differences in household ( n = 1303) livelihood strategies within VCA villages in 2016. The analysis finds that VCA villages contained significantly more forest loss than the most similar non-VCA villages outside the national park, and greater payments predict increased forest loss in the post-project period. In addition, farming high-value tree crops and cultivating private land were the most important attributes for modeling VCA affiliation among randomly selected households. These results demonstrate that, after payments ceased, project failures increased in severity over time.Those who design and implement conservation-based payments bear great responsibility to ensure their projects are informed by local voice, align with community preferences, and provide sufficient benefits, lest they result in a conservation legacy of increased failure.